1975
DOI: 10.1111/j.1476-5381.1975.tb07422.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF DOPAMINE ON SINUS RATE AND VENTRICULAR CONTRACTILE FORCE OF THE DOG HEART in vitro AND in vivo

Abstract: 1 Experiments were carried out on dog isolated papillary muscle and sinus node preparations perfused with arterial blood from a donor dog. The chronotropic and inotropic effects of dopamine were analysed by using reserpine, desmethylimipramine (DMI), cocaine and phenoxybenzamine, and the relative chronotropic and inotropic effects defined, the results being compared with those for noradrenaline (NA). 2 The effects of dopamine administered intra-arterially into the isolated preparations were reduced by pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
2
11
1
Order By: Relevance
“…Blood-perfused papillary muscle and sinus node preparations Details of the experimental procedures for preparing the blood-perfused preparations have been given previously (Endoh, 1975). The anterior papillary muscle and the sinus node region were perfused by means of a peristaltic pump (separately, through the cannulated anterior septal artery and the sinus node artery, respectively) with arterial blood from a donor dog at a constant perfusion pressure of 100 mmHg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood-perfused papillary muscle and sinus node preparations Details of the experimental procedures for preparing the blood-perfused preparations have been given previously (Endoh, 1975). The anterior papillary muscle and the sinus node region were perfused by means of a peristaltic pump (separately, through the cannulated anterior septal artery and the sinus node artery, respectively) with arterial blood from a donor dog at a constant perfusion pressure of 100 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…Since it has been shown that the positive inotropic action elicited by stimulation of a-adrenoceptors in the mammalian heart depends very much on the experimental conditions (Nakashima et al, 1973;Endoh & Schumann, 1975a;Endoh, et al, 1975;Ledda et al, 1975;Mugelli et al, 1976;Kunos, 1977;Kunos & Nickerson, 1977), in this study the ventricular myocardium and sinus node of the dog were maintained under near physiological conditions (Endoh, 1975) by perfusing with arterial blood from a donor dog. The actions of PE were then compared with those of Iso.…”
Section: Blood-perfused Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that other functional proteins such as myosin binding protein C and NCX are phosphorylated to potentially contribute to the regulation of Ca 2+ handling (11,12). Most sympathomimetic amines such as phenylephrine (20,23,24), dopamine (21,46), norepinephrine, epinephrine (46), isoproterenol (22), dobutamine (25), and denopamine (26) ] o (9). This may be partly due to a decrease in myofilament Ca 2+ sensitivity in relation to troponin I phosphorylation and abbreviation of Ca 2+ transients due to activation of SERCA2a.…”
Section: -1 β-Adrenoceptor Stimulationmentioning
confidence: 99%
“…To clarify whether these inotropic effects of DA as well as the chronotropic ones are direct actions on the cardiac muscles or indirect ones by releasing noradrenaline (NA) from the sympathetic nerve terminals in the cardiac muscles, the sympathetically denervated preparations by the treatments with reserpine [7][8][9][10][11][12] or 6-hydroxydopamine (6-OHDA) [13][14][15] were used, as reported previously. To the author's knowledge, it remains unknown whether the arrhythmogenic effects of DA could be produced by the direct or indirect actions.…”
mentioning
confidence: 99%